The effect of motivation and learning discipline on student learning outcomes in online-based Buddhist religious education subjects - Mujiyanto Mujiyanto (Ekspose: Jurnal Penelitian Hukum dan Pendidikan, 2022)
This study aims to determine the effect of learning motivation and learning discipline on student learning outcomes in the subject of Buddhist education using E-Learning learning. This study uses a quantitative approach with the ex post facto method, the nature of the ex post facto is that there is no control over the variables. The sample of this study consisted of junior high school Buddhist religious education students in Semarang district. The data in this study were obtained through non-test techniques in the form of questionnaires and also documentation techniques in the form of student learning outcomes in Buddhist subjects. The data in this study were analyzed using inferential statistical analysis techniques, namely multiple regression analysis. The results of this study indicate that there is a significant influence between students' motivation and learning discipline simultaneously on student learning outcomes in e-learning-based Buddhist subjects (0.00 0.05); and the magnitude of the joint contribution between motivation and student learning discipline on student learning outcomes in e-learning-based Buddhist subjects is 75%.